Investigation of Low-Frequency Sound Radiation Characteristics and Active Control Mechanism of a Finite Cylindrical Shell - Shaohu Ding; Chunyang Mu; Yang Gao; Hong Liu; Maoqiang Li (Shock and Vibration)
In this paper, the radiation characteristics and active structural acoustic control of a submerged cylindrical shell at low frequencies are investigated. First, the coupled vibro-acoustic equations for a submerged finite cylindrical shell are solved by a modal decomposition method, and the radiation impedance is obtained by the fast Fourier transform. The modal shapes of the first ten acoustic radiation modes and the structure-dependent radiation modes are presented. The relationships between the vibration modes and the radiation modes as well as the contributions of the radiation modes to the radiated sound power are given at low frequencies. Finally, active structural acoustic control of a submerged finite cylindrical shell is investigated by considering the fluid-structure coupled interactions. The physical mechanism of the active control is discussed based on the relationship between the vibration and radiation modes. The results showed that, at low frequencies, only the first several radiation modes contributed to the sound power radiated from a submerged finite cylindrical shell excited by a radial point force. By determining the radiation modes that dominate the contribution to the radiated sound, the physical mechanism of the active control is explained, providing a potential tool to allow active control of the vibro-acoustic responses of submerged structures more effectively.